Examining the Linkage between Students’ Participation in Co-curricular Activities and their Soft Skill Development - Md. Roknuzzaman Siddiky (Journal of Educational Sciences, 2020)
The paper aims to investigate the association between students’ participation in Co-curricular Activities (CCAs) and their soft skill development. Moreover, the study attempts to find out whether the association between these two variables is statistically significant. The study reasonably employed survey method where primary data were collected from a total of 135 students who were sampled from 16 academic departments of a public university in Bangladesh based on non-probability sampling techniques. The study found that the students have developed diverse soft skills (which involve different personal skills and social skills) much via their participation in CCAs. The study observed that there is a moderate positive association between students’ participation in CCAs and their various personal and social skills excepting presentation skill, organizing skill and network-building skill in which strong positive association was found. Moreover, the study found that there is a significant association between students’ participation in CCAs and their diverse personal skills and social skills. Hence, the study argued that the association between students’ participation in CCAs and their soft skill development is statistically significant. Finally, the study suggested that the Government and the authority concerned should undertake suitable policy in order to utilize CCAs and thereby ensure quality education.